Members of the 30- to 32-kilodalton mycolyl transferase family (Ag85) from culture filtrate of Mycobacterium avium subsp. paratuberculosis are immunodominant Th1-type antigens recognized early upon infection in mice and cattle16 - Rosseels,V.; Sylvie Marché; Virginie Roupie; M. Govaerts; Godfroid,J.; Walravens,K.; K Huygen (Infect.Immun., 2006)
The characterization of protective antigens is essential for the development of an effective, subunit-based vaccine against paratuberculosis. Surface-exposed and secreted antigens, present abundantly in mycobacterial culture filtrate (CF), are among the well-known protective antigens of Mycobacterium tuberculosis and Mycobacterium bovis. Culture filtrate, prepared from Mycobacterium avium subsp. paratuberculosis ATCC 19698 grown as a surface pellicle on synthetic Sauton medium, was strongly and early recognized in experimentally infected B6 bg/bg beige mice and cattle, as indicated by elevated spleen cell gamma interferon (IFN-gamma) secretion and lymphoproliferative responses of peripheral blood mononuclear cells, respectively. Strong proliferative and ex vivo IFN-gamma responses against antigen 85 (Ag85) complex (a major protein component from M. bovis BCG culture filtrate) could be detected in cattle as early as 10 weeks after oral M. avium subsp. paratuberculosis infection. Synthetic peptides from the Ag85A and Ag85B components of this complex were strongly recognized, whereas T-cell responses were weaker against peptides from the Ag85C protein. A promiscuous T-cell epitope spanning amino acids 145 to 162 of Ag85B (identical sequence in M. bovis and M. avium subsp. paratuberculosis) was identified in experimentally infected cattle. Finally, young calves, born from cows with confirmed paratuberculosis, demonstrated proliferative responses to purified, recombinant Ag85A and Ag85B from M. avium subsp. paratuberculosis. These results indicate that the M. avium subsp. paratuberculosis Ag85 homologues are immunodominant T-cell antigens that are recognized early in experimental and natural infection of cattle
Keywords: 0; a; acid; Acids; Acyltransferases; Amino acids; an; Animals; Antigens; Antigens,Bacterial; article; AS; BCG; Belgium; biosynthesis; blood; Born; Brussels; Cattle; Cell; Cell Proliferation; cells; Cells,Cultured; Components; culture; Development; effective; Epitopes; families; Family; growth & development; im; Immunodominant Epitopes; immunology; INFECTION; Institute; Interferon-gamma; IS; journal; Laboratories; Lymphocyte Activation; M; Male; MEDIA; metabolism; mice; Mice,Inbred C57BL; Mice,Mutant Strains; microbiology; Molecular Weight; Mycobacterium; Mycobacterium avium subsp.paratuberculosis; Mycobacterium bovis; Mycobacterium tuberculosis; ON; Paratuberculosis; pathology; Peptides; present; Print; protein; recombinant; Research; Research Support; response; Responses; result; results; SB - IM; secretion; Spleen; Synthetic; Th1 Cells; Tuberculosis; vaccine; young